Characterizing wind pressure on CAARC standard tall building with various façade appurtenances: An experimental study. (1st November 2022) - Chen, F.B.; Liu, H.M.; Chen, W.; Shu, Z.R.; Li, Y.; Li, Q.S.; Han, Y.
Abstract: Tall buildings are usually considered as wind-sensitive structures. While extensive studies have been conducted concerning the wind load characteristics on tall buildings, the effect of façade appurtenances has not been fully understood. In this study, a 1:300 scaled CAARC (Commonwealth Advisory Aeronautical Research Council) standard tall building was tested in wind tunnel to diagnose the effect of various façade appurtenances on wind pressure characteristics. It is shown that, the change of façade appurtenances can significantly influence the fluctuating wind pressure on the windward and leeward surfaces, with the maximum reduction reaching 21%. By contrast, the effect of façade appurtenance on mean wind pressure is somewhat less pronounced. The results also indicated that adding vertical strips is likely to reduce the horizontal coherence of surface wind pressure, with the maximum reduction of horizontal coherence coefficient reaching 38%. Comparatively, the effect of façade appurtenance on vertical coherence is less significant. Highlights: The effect of facade appurtenance on tall building wind pressure was examined. The fluctuating wind pressures on windward/leeward surfaces depend strongly on facade appurtenance. Façade appurtenances exhibits little effect on mean wind pressure. The facade appurtenance indicates more pronounced effect on horizontal coherence.